Illness as a space of communication between man and God as perceived by the Old Russian scribe (11–13th cc.) - Natalia Pelezneva (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
Based on Old Russian literary sources of 11-13th cc., this paper examines how illness was perceived in the Middle Ages. This research concentrates on a certain perception type (“communication illness”) and describes its distinctive features. This type of sickness integrates several versions of the medieval illness etiology, including “illness as a punishment” and “illness as a trial”. The author suggests that an Old Russian scribe considered “communication illness” as a message from God. The circumstances of the illness allowed the sick person to recognize the situation of “communication” and decipher the message. Some details like visions or the absence of “sickness agents” could help to recognize this type of illness. The research distinguishes several subtypes of “communication illness”, which are called “sign illness”, “punishment illness”, “inborn illness” and “deathbed illness”. The last one could be perceived as an ascetic practice available to both clergy and laity. Scribes condemned any attempt to feign a “communication illness”, this was viewed as an act of sacrilege. The message of “communication illness” was more often positive, it was perceived as a sign of God’s favor to the sick person. Biblical quotations used in descriptions of the illness show that “communication illness” was closely related to the virtue of patience. The conclusions of this research make it possible to correct the present conception that Old Russian scribes prohibited any attempts to apply methods of classical (Hippocratic) medicine. The author believes that scribes condemned Hippocratic methods exclusively in the situations of “communication illness”, in other cases of sickness they had no objection to a classical approach to the treatment.